The SMRT Corepressor Is Regulated by a MEK-1 Kinase Pathway: Inhibition of Corepressor Function Is Associated with SMRT Phosphorylation and Nuclear Export - Hong, Suk-Hyun (American Society for Microbiology, 2000)
The SMRT (silencing mediator of retinoic acid and thyroid hormone receptor) corepressor participates in the repression of target gene expression by a variety of transcription factors, including the nuclear hormone receptors, promyelocytic leukemia zinc finger protein, and B-cell leukemia protein 6. The ability of SMRT to associate with these transcription factors and thereby to mediate repression is strongly inhibited by activation of tyrosine kinase signaling pathways, such as that represented by the epidermal growth factor receptor. We report here that SMRT function is potently inhibited by a mitogen-activated protein kinase (MAPK) kinase kinase (MAPKKK) cascade that operates downstream of this growth factor receptor. Intriguingly, the SMRT protein is a substrate for phosphorylation by protein kinases operating at multiple levels in this MAPKKK pathway, including the MAPKs, MAPK–extracellular signal-regulated kinase 1 (MEK-1), and MEK-1 kinase (MEKK-1). Phosphorylation of SMRT by MEKK-1 and, to a lesser extent, MEK-1 inhibits the ability of SMRT to physically tether to its transcription factor partners. Notably, activation of MEKK-1 or MEK-1 signaling in transfected cells also leads to a redistribution of the SMRT protein from a nuclear compartment to a more perinuclear or cytoplasmic compartment. We suggest that SMRT-mediated repression is regulated by the MAPKKK cascade and that changes both in the affinity of SMRT for its transcription factors and in the subcellular distribution of SMRT contribute to the loss of SMRT function that is observed in response to kinase signal transduction.